2018
DOI: 10.1002/jcla.22449
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of phosphorus and urea as indices of their plasma levels in nephropathic patients

Abstract: S-Pho and S-Urea reflect plasma phosphorus and plasma urea. Early morning fasting fresh samples are advisable because collection time and freezing-thawing affect saliva tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…This is an observational study that was performed in accordance with the ethical principles of the Declaration of Helsinki and was approved by the local institutional Ethics Committees (n. 5/2012 and 4/2013). The study was included in a collaboration project developed by the Italian Space Agency ( Agenzia Spaziale Italiana , ASI) and the National Aeronautics and Space Administration (NASA) for investigation on the use of saliva in the monitoring of metabolic changes during space mission (https://www.nasa.gov/mission_pages/station/research/experiments/explorer/Investigation.html?#id=304), [19, 20]. The study enrolled healthy volunteers of the department personnel for analyses on methodological aspects and patients with chronic kidney disease (CKD) of the outpatient clinic of the University Hospital for analyses on associations saliva/plasma as previously reported [19].…”
Section: Methodsmentioning
confidence: 99%
“…This is an observational study that was performed in accordance with the ethical principles of the Declaration of Helsinki and was approved by the local institutional Ethics Committees (n. 5/2012 and 4/2013). The study was included in a collaboration project developed by the Italian Space Agency ( Agenzia Spaziale Italiana , ASI) and the National Aeronautics and Space Administration (NASA) for investigation on the use of saliva in the monitoring of metabolic changes during space mission (https://www.nasa.gov/mission_pages/station/research/experiments/explorer/Investigation.html?#id=304), [19, 20]. The study enrolled healthy volunteers of the department personnel for analyses on methodological aspects and patients with chronic kidney disease (CKD) of the outpatient clinic of the University Hospital for analyses on associations saliva/plasma as previously reported [19].…”
Section: Methodsmentioning
confidence: 99%
“…Saliva mainly consists of water, which represents up to 99% of its total volume. In addition, studies on human and veterinary species have reported that saliva also contains compounds such as phosphorus (P), lactate, cholesterol, fatty acids, glucose, hormones such as cortisol, triglycerides, urea and uric acid [1, 2]. In addition, saliva has enzymes such as salivary alpha-amylase (sAA), lipase, carbonic anhydrase, adenosine deaminase (ADA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and creatine kinase (CK), among others [3–8].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the salivary urea of nephropathic individuals with normal individuals, it was identified in the first hour of fasting that the two samples presented a very high value when compared to blood urea [52]. Bearing in mind the investigation and the need for greater scientific confirmation regarding a special group of individuals such as those in this study, our findings are consistent with previous reports, even though in other categories we infer that it is important to highlight the possibility of using salivary creatinine and urea analysis for diagnosis and evaluation, not only of chronic kidney disease but also of acute renal disease, especially in polytrauma patients [18,19,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all the aforementioned functions, calcium, along with other minerals, promotes the maintenance of the isoelectric point of proteins, bone mineralization, transmission of nerve impulses, maintenance of the contraction mechanism and relaxation of the muscles, and also regulation of the ionic balance effect in enamel remineralization [52,65], thus guaranteeing temporary oral health in the patient. Because it is a transient state of high calcium, it also increases individuals’ susceptibility to dental calculus formation.…”
Section: Discussionmentioning
confidence: 99%